Alcohol Dehydrogenases with anti‐Prelog Stereopreference in Synthesis of Enantiopure Alcohols. Issue 4 (22nd February 2022) - Musa, Musa M.
Abstract: Biocatalytic production of both enantiomers of optically active alcohols with high enantiopurities is of great interest in industry. Alcohol dehydrogenases (ADHs) represent an important class of enzymes that could be used as catalysts to produce optically active alcohols from their corresponding prochiral ketones. This review covers examples of the synthesis of optically active alcohols using ADHs that exhibit anti ‐Prelog stereopreference. Both wild‐type and engineered ADHs that exhibit anti ‐Prelog stereopreference are highlighted. Abstract : Alcohol Dehydrogenases (ADHs) with anti ‐Prelog stereopreference, both wild‐type and engineered, can be used for asymmetric reductions of prochiral ketones. Findings and insights that might guide researchers to construct more ADHs with anti ‐Prelog stereopreference are critically reviewed in this contribution.